Performances obtained using a full mechanized complex at Lupeni colliery - Romania - Radu, S. M.; Petrar, A. P.; Jujan, C.; Hoara, M.; Hanumolo, C. (НТУ "ХПИ", 2010)
In article results of research of operation of the mechanized complex on mine Lupen are considered. After brief presentation of mountain-geological and operational conditions, and also design data-operational of a complex, in the ratio with the received results, a number of conclusions which promote improvement of operational characteristics of the given complex is resulted.

In article results of research of operation of the mechanized complex on mine Lupen are considered. After brief presentation of mountain-geological and operational conditions, and also design data-operational of a complex, in the ratio with the received results, a number of conclusions which promote improvement of operational characteristics of the given complex is resulted.
Результаты исследований, полученные механизированным комплексом на шахте Лупень – Румыния
Keywords: mechanized complex; mine; operational conditions; operational characteristics; шахта; механизированный комплекс; операционные условия; конструктивно-эксплуатационные параметры